An improved version of artificial boundary node approach - Kanber, Bahattin (Computer Assisted Methods in Engineering and Science, 2022)
This paper proposes an improvement of the artificial boundary node approach using the least square method. The original artificial boundary node approach requires the selection of an offset by the user. The success of the original method depends on the correct choice of the offset. However, the improved version uses a least square line and the solution does not depend on a single offset. The solution is carried on using at least two different offsets and final solution is obtained by replacing the offset as zero in the least square equation. The improved version supplies good accuracy and stability in the boundary element solution. Three different case studies are solved to validate proposed method in 2-D elasticity. All results are compared with each others, conventional BEM, FEM, ANSYS and analytical results whenever possible.